(untitled) (Texas Journal of Medical Science, 2022)
Despite the successes of modern surgery, bacterial abscesses remain one of the most complex complications in surgical hepatology [4]. Traditionally used methods of surgical interventions are quiteremoteand, often, insufficiently adequate, especially with multiple abscesses, as well as with the development of sepsis. Combination with minimally invasive techniques (in the form of interventions under the control of radiation navigation (ultrasound, X-ray), endoscopy and laparoscopy) can significantly improve the results of treatment of this category of patients